Influential factors for successful knowledge transfer in restaurant franchises. (March 2021) - Moon, Hyeyoung; Ham, Sunny; Kim, Seung-Chul; Lee, Bo Youn
Abstract: This study examines the factors that influence successful knowledge transfer (KT) in restaurant franchises. First, this study aims to identify the relationships among franchisors' capabilities of KT, franchisees' willingness to acquire knowledge, and franchisees' performance. Second, it is to identify the mediation effects of franchisees' willingness to engage on KT. Third, it is to examine a moderating effect of restaurant type on the relationship between franchisors' capabilities of KT and franchisees' willingness to acquire KT. Data was collected from 119 franchisees. The results suggest that when franchisors have greater capability and willingness to transfer knowledge and comply with policies for KT, franchisees' willingness to acquire KT increases. Further, franchisees' willingness to acquire knowledge have a positive effect on their performance of KT. Franchisees' willingness to acquire knowledge also mediates the relationship between franchisors' capabilities and franchisees' performance of KT. Finally, restaurant type moderates the relationship between franchisors' capabilities of KT and franchisees' willingness to acquire knowledge.